Unequal treaties, consular jurisdiction, and treaty port society - Fuess, Harald (Routledge handbook of modern Japanese history, 2017)
Western extraterritoriality in Meiji Japan was mostly seen as a symbol of Western imperialism violating Japanese sovereignty and territorial integrity. The revision of the unequal treaties thus became the overarching policy goal of successive Japanese governments. Although the image of Japan’s coerced and unwanted foreign relations is perpetuated by terms such as ‘the opening of Japan’ and ‘unequal treaties’, Western historians of Japan have given little attention to the actual workings of extraterritoriality in Japanese treaty ports. This chapter discusses extraterritorial rights of Great Britain and the United States while paying due attention to the hitherto neglected role of Germany and France. In particular, it explores the workings of the system of consular jurisdiction to argue that it helped to order and regulate the lives in Japanese treaty ports such as Yokohama across national boundaries and thereby may have contributed to a containment of Western imperialism in Meiji Japan.
Gesehen am 07.07.2022